THE INFLUENCE OF BUDDHIST PRINCIPLES ON ORGANIZATIONAL ADMINISTRATION OF THE STATE ENTERPRISE WHICH RECEIVED EXCELLENCE MANAGEMENT AWARD AND HAVING THE NUMBER ONE INCOME IN THE COUNTRY - Ngamsompark, Prat; Pooripakdee, Santidhorn (Journal of Buddhist Anthropology, 2020)
This paper aims to study the Influence of Buddhist principles on organizational administration of the state enterprise which received excellence management award and having the number one income in the country in the direct effect and indirect effect of the mediating variables including burnout, job satisfaction, organizational citizenship behavior and organizational commitment with the quantitative method. The study population was staff of PTT Public Company Limited (PTT) amount 5,288. The samples are 389, sampled by Equal Probability Sampling and Simple Random Sampling (SRS). The study instrument was a set of questionnaires. Using structural equation modeling (SEM), descriptive statistics and inferential statistics to analyze data. The result shows that there was consistency between the structural equation model and the empirical data; the derived values were; Chi-square = 98.80, P-value = 0.10, Chi-square/df = 1.20, GFI = 0.98, AGFI = 0.95, CFI = 1.00 and RMSEA = 0.02. The result of study demonstrates that Buddhist principles on organizational administration have negative direct effect on individual work performance but have positive indirect effect instead when considered burnout, job satisfaction, organizational citizenship behavior and organizational commitment as partial mediators. The result from the study indicates that Buddhist principles on organizational administration can be practiced but the needs and values of employee have to be realized. To support those needs and values will lead to individual work performance.